2008
DOI: 10.1016/j.rapm.2007.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Epidural Anesthesia in Patients With Aortic Stenosis Undergoing Total Hip Replacement

Abstract: We report the absence of complications (with calculated upper limit 95% confidence interval of approximately 13.6%) when hypotensive epidural anesthesia was performed in 22 patients with noncritical asymptomatic aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…These findings concur with previous studies examining these risks in both maxillofacial and arthroplasty surgery [2,20]. Studies also show that hypotensive epidural anesthesia can be safely used in higher risk patients, including the elderly, and patients with hypertension, ischemic heart disease, or chronic renal impairment [7,17]. Lubrano et al [11] demonstrated a transient tubular dysfunction after induced hypotension with propofol and remifentanil (without concurrent adrenaline); however, a clear link to permanent renal dysfunction has not been demonstrated [17].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings concur with previous studies examining these risks in both maxillofacial and arthroplasty surgery [2,20]. Studies also show that hypotensive epidural anesthesia can be safely used in higher risk patients, including the elderly, and patients with hypertension, ischemic heart disease, or chronic renal impairment [7,17]. Lubrano et al [11] demonstrated a transient tubular dysfunction after induced hypotension with propofol and remifentanil (without concurrent adrenaline); however, a clear link to permanent renal dysfunction has not been demonstrated [17].…”
Section: Discussionsupporting
confidence: 82%
“…The technique, which involves a reduction in blood pressure while maintaining flow through stabilization of cardiac output, has demonstrated efficacy in lower limb orthopaedic surgery [7,[17][18][19][20]22], where it has been shown to reduce blood loss and transfusion reaction. Hypotensive epidural anesthesia provides sympathetic blockade by means of a high epidural anesthetic and sustained cardiac output by means of an adrenaline infusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venodilation has been a particular concern with epidural anesthesia, although recent studies suggest that this modality can be used safely. 5 Many anesthetic agents reduce systemic blood pressure and thereby reduce the aortic-coronary perfusion pressure gradient leading to reduced coronary blood flow. For surgical patients with significant AS, anesthetic management requires appropriate intravascular volume to optimize preload, heart rate control to allow adequate left ventricular filling along with time for coronary artery flow, and sufficient systemic blood pressure to maintain coronary artery blood flow.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Ho et al suggested the use of hypotensive epidural anaesthesia in patients with aortic stenosis undergoing total hip replacement and rendered satisfactory results provided that the stenosis is asymptomatic and non-critical. Nevertheless the choice of anaesthesia in such cases should be made on individual basis and in the presence of skilled anaesthetist [31].…”
Section: Epidural Blockmentioning
confidence: 99%